Teleoperation assistance through variable velocity mapping. - Dubey, R.V (IEEE Transactions on robotics and automation)
There has been increasing attention on human-machine cooperative teleoperation due to limited capabilities of autonomous robots. A method of sensor and model assisted teleoperation using variable velocity mapping is presented. The application of variable velocity mapping to the execution of Fitts tasks is described, and comparisons are made with traditional teleoperation. Application to a practical task of docking is also described